A unified approach to strategy-proofness for single-peaked preferences - John A. Weymark (SERIEs - Journal of the Spanish Economic Association, 2011)
This article establishes versions of Moulin's (Public Choice 35:437-455, 1980) characterizations of various classes of strategy-proof social choice functions when the domain consists of all profiles of single-peaked preferences on an arbitrary subset of the real line. Two results are established that show that the median of 2n +1 numbers can be expressed using a combination of minimization and maximization operations applied to subsets of these numbers when either these subsets or the numbers themselves are restricted in a particular way. These results are used to show how Moulin's characterizations of generalized median social choice functions can be obtained as corollaries of his characterization of minmax social choice functions.
Keywords: D71; D82; 330; generalized median social choice functions; Moulin minmax rules; single-peaked preferences; strategy-proofness; Soziale Wohlfahrtsfunktion; Asymmetrische Information; Theorie